Protective effects of pentoxifylline in pulmonary inflammation are adenosine receptor A2A dependent - Konrad, Franziska M.; Neudeck, Gianna; Vollmer, Irene; Ngamsri, Kristian C.; Thiel, Manfred; Reutershan, Joerg (The FASEB Journal, 2013)
Pentoxifylline (PTX) has been shown to exert anti-inflammatory effects in experimental acute lung injury. However, results in humans were controversial. Recent in vitro studies suggested that the adenosine receptor A2A may be required for PTX to be effective. Therefore, we studied the association between A2A and PTX in a murine model of LPS-induced pulmonary inflammation. PTX treatment (10 mg/kg) reduced cellular influx (by 40%), microvascular permeability (30%), and the release of chemotactic cytokines into the alveolar space (TNF-α 60%, IL-6 60%, and CXCL2/3 53%, respectively). These protective effects were abolished completely in A2A -/- mice and in wild-type mice that had been treated with the selective A2A antagonist (1 mg/kg), but effects were not different in mice with altered adenosine levels. In vitro transmigration assays revealed a pivotal role of the endothelium in PTX-mediated PMN migration, with a reduction of 50% (2 mM PTX). This effect was also A2A dependent. Further, oxidative burst of human PMNs was A2A-dependently reduced by 53% after PTX treatment. In summary, PTX exhibits its anti-inflammatory effects in LPS-induced lung injury through an A2Adependent pathway. These results will help to better understand previous conflicting data on PTX in inflammation and will direct further studies to consider the predominant role of A2A.-Konrad, F. M., Neudeck, G., Vollmer, I., Ngamsri, K. C., Thiel, M., Reutershan, J. Protective effects of pentoxifylline in pulmonary inflammation are adenosine receptor A2A dependent. © FASEB.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Migration; Neutrophils; Oxidative burst; Phosphodiesterase inhibitor; PTX